2017
DOI: 10.1590/1806-9061-2016-0372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Egg Weights on Hatching Results, Broiler Performance and Some Stress Parameters

Abstract: The present study was conducted to investigate the effect of hatching egg weight of broiler parent stocks on hatching results, chick performance, carcass characteristics, internal organ weights and some blood stress parameters. Eggs were divided into 3 egg weight groups (55.0 to 60.0 g (light), 60.1 to 65.0 g (medium) and 65.1 to 70.0 g (heavy)) for the experiments. After incubation, mixed-gender broiler chicks from the hatcher were placed into 27 grower pens (2x1 m) with 9 replications for 3 weight groups by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 27 publications
8
21
1
1
Order By: Relevance
“…This finding is consistent with the data reported by Abudabos et al (2017) for the incubation of eggs of autochthonous free-range chickens, and those by Duman and (2017) for the egg incubation of meattype hybrid. On the contrary, Rosa et al (2002) found a significantly higher total mortality in the group of large eggs of an average weight of 73.2 g (9.6%), compared to eggs of an average weight of 60.0 g (7.0%) and 65.1 g (6 , 7%), which is consistent with the results obtained by Iqbal et al (2016) Kopecký (2015) found the highest total mortality in the group of eggs weighing 70-75 g (16.7%), and the lowest in the group weighing 55-60 g (9.7%).…”
Section: Results Of Research and Discussionsupporting
confidence: 93%
“…This finding is consistent with the data reported by Abudabos et al (2017) for the incubation of eggs of autochthonous free-range chickens, and those by Duman and (2017) for the egg incubation of meattype hybrid. On the contrary, Rosa et al (2002) found a significantly higher total mortality in the group of large eggs of an average weight of 73.2 g (9.6%), compared to eggs of an average weight of 60.0 g (7.0%) and 65.1 g (6 , 7%), which is consistent with the results obtained by Iqbal et al (2016) Kopecký (2015) found the highest total mortality in the group of eggs weighing 70-75 g (16.7%), and the lowest in the group weighing 55-60 g (9.7%).…”
Section: Results Of Research and Discussionsupporting
confidence: 93%
“…In terms of overall hatchability and fertility, medium-sized eggs were better than large eggs whereas the small eggs' hatchability and fertility were comparable to both the medium and large size eggs. This is similar to the findings of Duman & Şekeroğlu (2017) who reported significantly higher hatchability in medium weight eggs than in larger sized eggs. Iqbal et al (2016) reported higher fertility and hatchability in medium-sized eggs than in larger eggs.…”
Section: Hatching Traitssupporting
confidence: 91%
“…Generally, the culled chicks are characterized by un-healed naval, week legs and other deformities. An earlier study from Duman & Şekeroğlu (2017) reported similar results showing a higher percentage of deformed chicks from larger sized eggs compared to medium-sized eggs but small-sized eggs were comparable to both egg weight categories in terms of deformed/culled chicks. Our results showed that the proportion of chicks with no defect/healthy chicks was significantly higher in medium-sized eggs compared to the large eggs.…”
Section: Hatching Traitssupporting
confidence: 55%
See 2 more Smart Citations